A unique approach to faculty development using an Observed Structured Teaching Encounter (OSTE). Issue 1 (1st January 2018) - Smith, Miriam A; Cherazard, Regine; Fornari, Alice; Adelman, Patti; Snopkowski, Michelle; Lesser, Martin
ABSTRACT: We have challenges with poor patient satisfaction scores (Hospital Consumer Assessment of Healthcare Providers and Systems [HCAHPS]) and internal medicine resident (IMR) evaluations of voluntary attending physicians. Using an Observed Structured Teaching Encounter (OSTE), we designed a faculty development project that focused on attendings' teaching and feedback skills. To assess attending communication with interns and improve attending teaching and feedback skills. All IM attendings on the Long Island Jewish Forest Hills (LIJFH) Emergency Department (ED) call schedule participated. OSTE simulation sessions included two clinical scenarios, standardized patients (SPs), fourth-year medical students trained as 'interns, ' OSTE checklists, and debriefing. We analyzed 'intern' ratings of communication with attendings and attending self-assessment during the OSTE, and attending HCAHPS scores and IMR evaluations of attendings pre- and post-OSTE. Twenty-nine of 29 attendings completed the OSTE. Although an increase was demonstrated pre- to post- for 'intern' OSTE ratings of attendings and LIJFH attending self-assessment ratings, there was no statistically significant difference. Mean HCAHPS scores and resident evaluations of attendings also increased from pre- (22% and 3.59) to post-OSTE (30% and 3.87) but did not reach statistical significance. A statistically significant difference for both cases was demonstrated when comparing mean attending self-assessment ratings with 'intern' evaluation of attendings. Attending teaching/feedback skills improved between cases, attending self-ratings were higher than 'intern' ratings of attendings. HCAHPS and IMR evaluations of attendings improved post-OSTE. Regular intervention utilizing an OSTE may provide a sustained benefit for enhancing attendings' skills, patient satisfaction, and resident training.